Rickettsia japonica Infections in Humans, Zhejiang Province, China, 2015 - Lu, Qunying (Emerg Infect Dis, 2018)
We investigated 16 Japanese spotted fever cases that occurred in southeastern China during September–October 2015. Patients had fever, rash, eschar, and lymphadenopathy. We confirmed 9 diagnoses and obtained 2 isolates with high identity to Rickettsia japonica strain YH. R. japonica infection should be considered for febrile patients in China.